STRATEGIC STEPS TO IMPLEMENT ACTIVITIES TO INFORM THE PUBLIC ABOUT THE RISKS OF COVID-19 (Herald of the National Children's Medical Center, 2022)
Protecting and strengthening the health of the nation – including mass public health campaigns have a direct link inobtaining the desired effect in reducing the frequency and burden of morbidity, which is mostly directly related to changingpeople’s behavior. It is quite difMcult to achieve this, but it is possible through its prerequisites: raising awareness not onlyabout diseases, but also ways to prevent them, disseminate knowledge and change psychological attitudes.
Keywords: COVID-19; quality management; awareness